PENGARUH PEMANFAATAN OFFICE AUTOMATION WEBMAIL DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT GIKEN PRECISION INDONESIA DI KOTA BATAM - tukino tukino (Universitas Putera Batam, 2015)
This study aimed to examine the effect of Utilization Office Automation Webmail and Motivation on Employee Productivity. Employee productivity can be interpreted as a result of the company or individual in carrying out the work effectively, efficiently and legally controlled conducted in order to achieve the mission and vision of the company. Factors that may affect the Employee Productivity allegedly dominant enough to have an influence on Employee Productivity at PT Giken Precision Indonesia in Batam are Utilization Office Automation Webmail and Motivation. These factors are interrelated to each other on Employee Productivity at PT Giken Precision Indonesia in Batam. Thus these factors have a relationship that can be combined to achieve Employee Productivity is high. Employee productivity is influenced by many other factors that need to augment existing theories. This study is expected to provide input to the company that optimize utilization of Office Automation Webmail can improve Employee Productivity. Good service quality is highly dependent on the provider that indeed competent in their field. By processing the data using statistical tests, the results of this study suspected Utilization Office Automation Webmail very useful for service, motivation is very beneficial for the service, useful for service productivity, and partially that the utilization of Office Automation Webmail significant effect on Employee Productivity and Motivation significant effect on Employee productivity, as well as the simultaneous utilization of Office Automation Webmail and motivation influence on Employee Productivity.